In vitro differentiated human CD4+ T cells produce hepatocyte growth factor - Ford, Shayne Lavondua; Buus, Terkild Brink; Nastasi, Claudia; Geisler, Carsten; Bonefeld, Charlotte Menné; Ødum, Niels; Woetmann, Anders (Frontiers in Immunology, 2023)
Differentiation of naive CD4+ T cells into effector T cells is a dynamic process in which the cells are polarized into T helper (Th) subsets. The subsets largely consist of four fundamental categories: Th1, Th2, Th17, and regulatory T cells. We show that human memory CD4+ T cells can produce hepatocyte growth factor (HGF), a pleiotropic cytokine which can affect several tissue types through signaling by its receptor, c-Met. In vitro differentiation of T cells into Th-like subsets revealed that HGF producing T cells increase under Th1 conditions. Enrichment of HGF producing cells was possible by targeting cells with surface CD30 expression, a marker discovered through single-cell RNA-sequencing. Furthermore, pharmacological inhibition of PI3K or mTOR was found to inhibit HGF mRNA and protein, while an Akt inhibitor was found to increase these levels. The findings suggest that HGF producing T cells could play a role in disease where Th1 are present.